Interpreting behaviors from accelerometry: a method combining simplicity and objectivity. Issue 20 (2nd October 2015) - Collins, Philip M.; Green, Jonathan A.; Warwick‐Evans, Victoria; Dodd, Stephen; Shaw, Peter J. A.; Arnould, John P. Y.; Halsey, Lewis G.
Abstract Quantifying the behavior of motile, free‐ranging animals is difficult. The accelerometry technique offers a method for recording behaviors but interpretation of the data is not straightforward. To date, analysis of such data has either involved subjective, study‐specific assignments of behavior to acceleration data or the use of complex analyses based on machine learning. Here, we present a method for automatically classifying acceleration data to represent discrete, coarse‐scale behaviors. The method centers on examining the shape of histograms of basic metrics readily derived from acceleration data to objectively determine threshold values by which to separate behaviors. Through application of this method to data collected on two distinct species with greatly differing behavioral repertoires, kittiwakes, and humans, the accuracy of this approach is demonstrated to be very high, comparable to that reported for other automated approaches already published. The method presented offers an alternative to existing methods as it uses biologically grounded arguments to distinguish behaviors, it is objective in determining values by which to separate these behaviors, and it is simple to implement, thus making it potentially widely applicable. The R script coding the method is provided.